Synthesis of single layer graphene on Cu(111) by C60 supersonic molecular beam epitaxy. Issue 44 (18th April 2016) - Tatti, Roberta; Aversa, Lucrezia; Verucchi, Roberto; Cavaliere, Emanuele; Garberoglio, Giovanni; Pugno, Nicola M.; Speranza, Giorgio; Taioli, Simone
Abstract : High kinetic energy impacts between inorganic surfaces and molecular beams seeded by organics represent a fundamental tool in materials science, particularly when they activate chemical–physical processes leading to nanocrystals' growth. Abstract : High kinetic energy impacts between inorganic surfaces and molecular beams seeded by organics represent a fundamental tool in materials science, particularly when they activate chemical–physical processes leading to nanocrystals' growth. Here we demonstrate single-layer graphene synthesis on copper by C60 supersonic molecular beam (SuMBE) epitaxy. A growth temperature down to 645 °C, lower than that typical of chemical vapour deposition (1000 °C), is achieved by thermal decomposition of C60 with the possibility of further reduction. Using a variety of electron spectroscopy and microscopy techniques, and first-principles simulations, we describe the chemical–physical mechanisms activated by SuMBE and assisted by thermal processes, resulting in graphene growth. In particular, we find a role of high kinetic energy deposition in enhancing the organic/inorganic interface interaction and controlling the fullerene cage openings. These results, while discussed in the specific case of graphene on copper, are potentially extendible to different metallic or semiconductor substrates and where lower processing temperature is desirable.